Perceptions and beliefs about anaemia: A qualitative study in three agroecological regions of Ghana - Raphael Baffour Awuah; Esi K. Colecraft; Mark L. Wilson; Leonard Kofi Adjorlolo; Nathalie J. Lambrecht; Hanson Nyantakyi‐Frimpong; Andrew D. Jones (Wiley, 2021)
Abstract Little evidence exists concerning perceptions of anaemia in Ghanaian communities, which limits understanding of how to potentially improve health in settings with high anaemia prevalence. We explored lay perceptions of anaemia to understand local knowledge and beliefs and to provide an opportunity to inform interventions. A cross‐sectional, qualitative study was conducted in selected communities in three regions of Ghana with high prevalence of anaemia. Forty‐eight focus group discussions (FGDs) were conducted with adolescent girls, adult women of reproductive age and adult men (16 FGDs for each demographic group). Participants across the three demographic groups generally described anaemia as inadequate blood in the body and reported that poor diet, heat, alcohol intake, physiological factors and diseases such as malaria were the main causes of anaemia. Consequences of anaemia mentioned in the FGDs included dizziness, weight loss, loss of appetite and weakness. Prevention of anaemia was perceived to result from improved diet, avoidance of exposure to heat and improved sanitation to avoid diseases. The findings suggest that despite areas of convergence between lay and biomedical knowledge on the causes, consequences and prevention of anaemia, the burden of anaemia remains high in the study regions. This highlights a disconnect between local knowledge of anaemia and the health and nutrition behaviours needed to reduce its incidence. Effective interventions can be developed with and for communities that build upon existing knowledge while filling remaining knowledge gaps or misconceptions.